2011
DOI: 10.1016/j.heares.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of experimentally induced conductive hearing loss on spectral and temporal aspects of sound transmission through the ear

Abstract: Conductive hearing loss (CHL) is known to produce hearing deficits, including deficits in sound localization ability. The differences in sound intensities and timing experienced between the two tympanic membranes are important cues to sound localization (ILD and ITD, respectively). Although much is known about the effect of CHL on hearing levels, little investigation has been conducted into the actual impact of CHL on sound location cues. This study investigated effects of CHL induced by earplugs on cochlear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 88 publications
4
28
0
Order By: Relevance
“…Maximum mean ITD observed was 324µs, remarkably similar to the 330 µs observed by Sterbing et al (2003). As predicted by Kuhn (1977), and consistent with the data from cats (Roth et al, 1980) and chinchilla (Koka et al, 2011; Lupo et al, 2011) the low frequency ITDs in the guinea pig were ~50% larger than the high frequency ITDs.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Maximum mean ITD observed was 324µs, remarkably similar to the 330 µs observed by Sterbing et al (2003). As predicted by Kuhn (1977), and consistent with the data from cats (Roth et al, 1980) and chinchilla (Koka et al, 2011; Lupo et al, 2011) the low frequency ITDs in the guinea pig were ~50% larger than the high frequency ITDs.…”
Section: Resultssupporting
confidence: 87%
“…Previous results suggest that ITDs are larger for low- than high-frequency sounds in humans (Kuhn 1977) and animals (chinchilla: Koka et al 2011; Lupo et al 2011; cat: Roth et al 1980; guinea pig: Sterbing et al 2003). The analysis of ITD as in Section 3.2.3 obscures the possible frequency dependence of ITD.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The resulting acoustic waveforms were simultaneously recorded in the left and right ear canals using two probe tube microphones, amplified, collected using two analog to digital converter channels, and stored for off-line analysis. Measurements made previously in the lab (e.g., Lupo et al 2011) demonstrated that the chamber is effectively anechoic for frequencies down to 250 Hz. An acoustic calibration measurement was also made in the absence of the animal to capture the spectral characteristics of the loudspeakers and microphones.…”
Section: Methodsmentioning
confidence: 95%
“…It is clear that peripheral hearing loss affects the BIC via amplitude reduction or peak latency delay. Laska et al (1992) noted that in the adult animals that experienced a 4-week monaural or binaural temporary conductive hearing loss, the conduction delay caused by the earplug (see also Lupo et al, 2011) resulted in an immediate temporary latency increase that resolved upon occlusion removal. In one subject showing a combined low-frequency and high-frequency hearing loss, Wrege and Starr (1981) similarly found a longer BIC latency compared to no latency effect for high-frequency hearing loss alone.…”
Section: Potential For the Bic Of The Abr As A Diagnostic Toolmentioning
confidence: 99%